The Waqf of the Great al-Omari Mosque in Sidon (1844-1908) - Çelik, Kürşat (T.C. Vakıflar Genel Müdürlüğü, 2024)
Nowadays, Sidon is located within the borders of Lebanon. The city, which has an ancient past, has been under the rule of many states throughout history. It was conquered by the Muslims during the reign of Omar and came under Ottoman rule during Sultan Selim I’s expedition to Egypt in 1516. The city remained Ottoman until the French invasion in 1918. After Sidon was conquered by the Ottomans, the waqfs in the city were recorded. The Ottoman Empire made the necessary efforts to maintain the existence of waqfs that had preceded it, and as a result, the waqfs continued their existence until the last period of the empire. Based on waqf accounting books covering the period 1844-1908, the study offers information on income items, type, and number of expenses, and the title and wages of the employees working at the waqf of the Great al-Omari Mosque. The main purpose of this research is to analyze the economic structure of the aforementioned waqf in the last period of the Ottoman Empire, and to reveal the place of the foundation in the city economy as well as the social and economic changes in the services provided over time. The study also reveals how the waqfs that were damaged as a result of natural disasters and whose economic power was insufficient were reconstructed, and exposes the sensitivity of the state authorities to the work of waqfs.

Sayda, günümüzde Lübnan Devleti sınırları içerisinde bulunmaktadır. Bu şehir, kadim bir geçmişe sahip olup tarih boyunca çeşitli devletlerin hâkimiyeti altına girmiştir. Hz. Ömer döneminde Müslümanların kontrolüne geçmiş olan Sayda, Yavuz Sultan Selim’in 1516’daki Mısır seferiyle Osmanlı hâkimiyetine girmiştir. 1918 yılına kadar Osmanlı idaresinde kalan şehir, bu tarihten itibaren Fransızların işgaline uğramıştır. Sayda’nın, Osmanlı hâkimiyeti altına alınması ile birlikte şehirdeki vakıflar da kayıt altına alınmıştır. Osmanlı Devleti, kendinden önceki vakıfların varlığını sürdürmesi için gereken çaba ve gayreti göstermiş ve bunun neticesinde vakıflar Osmanlı’nın son dönemine kadar varlıklarını sürdürmüşlerdir. Bu çalışmada, 1844-1908 yılları arasındaki evkâf muhasebe defterlerine göre Sayda Hz. Ömer Camii vakfının gelir ve giderlerinin tür ve sayıları ile vakıfta çalışan personelin unvan ve almış oldukları ücretleri hakkında bilgi verilmiştir. Araştırmanın temel amacı Osmanlı Devleti’nin son dönemlerinde Sayda Hz. Ömer Camii Vakfı’nın ekonomik yapısının analizini yaparak, vakfın şehir ekonomisindeki yeri ile verdikleri hizmetlerde zaman içerisinde geçirmiş oldukları sosyal ve iktisadi değişimlerin ortaya çıkarılmasıdır. Bu çalışma ile doğal afetler sonucunda zarar gören ve ekonomik gücü yetersiz olan vakıfların nasıl ihya edildiği, devlet yetkililerinin vakıf eserlere karşı duyarlılığı tespit edilmiştir.
Sayda Hz. Ömer Camii (Camii-i Kebir) Vakfı 1844-1908
Keywords: Ottoman Institutions and Civilization (Other); Osmanlı Kurumları ve Medeniyeti (Diğer)